Foamy carbon composite coating electrode, preparation method thereof and lead flow battery

By sequentially plating copper and electrodepositing lead on the porous foam carbon electrode of the lead-flow battery, the foam carbon composite coating electrode is formed, which solves the shortcomings of traditional electrodes in terms of electrochemical activity, specific surface area, binding strength and stability, and achieves improvement of battery power storage performance and electrode multifunctionalization.

CN119518008APending Publication Date: 2025-02-25CHINA NAT PETROLEUM CORP +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311068810.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-23
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The traditional electrodes of lead-fluid flow batteries have shortcomings in electrochemical catalytic activity, electrochemical specific surface area, bonding strength of the electrode storage deposition layer, dendrite growth, conductivity and stability of the negative electrode Pb, resulting in small storage capacity, serious ohmic polarization, large redox potential difference, potential short-circuit potential risks, and problems of storage layer falling off.

Method used

The electroless copper plating and electrodeposition lead are sequentially performed on the porous foam carbon matrix to form a foam carbon composite coating electrode. By combining the intermediate copper plating layer and the electrodeposition lead layer, the conductivity and bonding strength of the electrode are enhanced and the stability of the electrode is improved.

Benefits of technology

The conductivity and storage capacity of the negative electrode are significantly improved, the bonding strength between the electrode and the storage deposition layer is enhanced, the side reactions during dendrites growth and electrode reaction are reduced, and the circulation efficiency and stability of the battery are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004410492960000111
    Figure BDA0004410492960000111
  • Figure BDA0004410492960000112
    Figure BDA0004410492960000112
  • Figure BDA0004410492960000121
    Figure BDA0004410492960000121
Patent Text Reader

Abstract

According to the foamy carbon composite coating electrode, the preparation method thereof and the lead flow battery, the chemical copper plating middle layer and the electrochemical deposition lead layer are sequentially compounded on the foamy carbon, and compared with a traditional carbon polymer graphite plate electrode, the conductivity of a negative electrode is greatly improved; the middle copper-plated layer enhances the bonding strength with the outer-layer electrodeposited lead in a metal bond and solid solution strengthening mode, the bonding strength of the outer-layer electrodeposited lead of the electrode and the same substance of the electricity storage Pb layer of the negative electrode after the battery is charged is higher, and the electricity storage deposited layer can be prevented from falling off; compared with a traditional carbon polymer graphite plate electrode, the composite coating electrode has no obvious corner angles and tips, the tip effect in the electro-deposition process is greatly eliminated, and dendritic crystal growth of a negative electrode electricity storage deposition layer Pb is restrained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of lead liquid flow batteries and relates to a foam carbon composite coating electrode and a preparation method thereof and a lead liquid flow battery. Background Art

[0002] The non-steady-state wind and solar power generation supporting energy storage technology is an important measure for my country to transform its energy consumption structure and achieve the goal of "carbon peak and carbon neutrality". Among them, the lead liquid flow battery is a diaphragm-free single liquid flow energy storage technology that integrates the characteristics of intrinsic safety, large capacity, low cost, long life, and power and capacity decoupling. The lead liquid flow battery system consists of three parts: a liquid storage tank, a circulation pump and a battery. The operation of the battery is realized by using a magnetic pump to push the electrolyte to circulate in the connected liquid storage tank, pipeline and battery to form a liquid flow loop. The positive / negative electrode reaction couple PbO2 / Pb in the battery 2+ and Pb 2+ / Oxidized or reduced Pb 2+ They are stored in Pb(CH3SO3)2 / CH3SO3H electrolyte. During charging, Pb 2+ At the negative electrode, the electrons provided by the external circuit are reduced to metal Pb and attached to the electrode surface. At the same time, at the positive electrode, the electrons are lost and oxidized to PbO2 and attached to the electrode surface, thus completing the conversion of electrical energy into chemical energy. During discharge, the solid deposited layers PbO2 and Pb on the positive / negative electrode surfaces gain / lose electrons on the plates, respectively, and are directly reduced and oxidized to Pb 2+ It enters the electrolyte to realize the conversion of chemical energy into electrical energy, and the reversible electrochemical reaction of charge and discharge completes the process of electricity storage and consumption.

[0003] At present, lead flow batteries mostly use traditional planar carbon polymer graphite plate electrodes, which have poor conductivity, resulting in severe ohmic polarization of the battery. The large redox potential difference of the battery results in low voltage efficiency. The small specific surface area of ​​the electrode results in small storage capacity. The tip effect makes the negative electrode storage Pb layer very easy to grow dendrites, posing the risk of short circuit between the positive and negative electrodes. The bonding strength between the negative electrode and the storage deposit layer is poor, and the flow of electrolyte easily causes dendrite breakage and Pb layer shedding, causing irreversible loss of battery capacity. Other electrodes, such as foam carbon electrodes, have shortcomings such as poor bonding strength with the surface of the storage deposit layer, low conductivity and low cycle efficiency. The hot-pressed titanium foam electrode on the carbon plate has significantly reduced its hot-pressing bonding stability after long-term operation, and also shows signs of corrosion in acidic electrolytes. Summary of the invention

[0004] In view of the shortcomings of the existing electrodes of the above-mentioned lead liquid flow battery, the present invention provides a foam carbon composite coating electrode and a preparation method thereof and a lead liquid flow battery. By respectively compounding different metal coatings on a porous foam carbon substrate, the shortcomings of the traditional negative electrode of the lead liquid flow battery in terms of electrochemical catalytic activity, electrochemical specific surface area, bonding strength of the storage deposit layer, dendrite growth of the negative electrode Pb, conductivity and stability are solved, thereby realizing the multifunctionality of the new electrode and improving the battery storage performance.

[0005] The present invention is achieved through the following technical solutions:

[0006] A method for preparing a foamed carbon composite coating electrode comprises the steps of chemically plating copper and electro-depositing lead on a porous foamed carbon substrate to prepare the foamed carbon composite coating electrode.

[0007] Preferably, the method for preparing the foam carbon composite coating electrode comprises:

[0008] The porous foam carbon substrate is sequentially pretreated by degreasing, roughening, sensitizing and activating;

[0009] Electroless copper plating on the pretreated porous carbon foam substrate;

[0010] Electrodeposition of lead on porous carbon foam substrate after electroless copper plating.

[0011] Furthermore, the roughening is specifically as follows: roughening the deoiled porous foam carbon matrix by ultrasonic treatment for 10-30 minutes in nitric acid with a mass fraction of 55%-75% at room temperature.

[0012] Furthermore, the sensitization is specifically as follows: treating the roughened porous foam carbon substrate in a sensitizing solution for 10-20 minutes, and then washing with water; the sensitizing solution formula is: concentrated HCl 40-55ml / L, SnCl2 30-40g / L and tin particles 4-8 particles / L.

[0013] Furthermore, the activation treatment is specifically as follows: activating the sensitized porous foam carbon substrate in an activation solution at room temperature for 15-35 minutes, and then taking it out to dry naturally; the activation solution formula is: PdCl2 0.53-0.62g / L and concentrated HCl 45-50ml / L.

[0014] Furthermore, the pretreated porous foam carbon substrate is pre-wetted with water and then subjected to chemical copper plating.

[0015] Furthermore, the chemical copper plating solution used in the chemical copper plating is formulated as follows: 20-25 g / L copper sulfate, 40-50 ml / L 24%-37% formaldehyde solution, 70-100 g / L potassium sodium tartrate, 10-15 g / L sodium hydroxide, 0.15-0.75 g / L 2-mercaptobenzothiazole, 1-3 g / L activated carbon, and 0.1-0.5 g / L EDTA.

[0016] Furthermore, the electrodeposited lead uses anode lead with a purity higher than 99.9%, and an anode bag is wrapped outside the anode lead.

[0017] Furthermore, the preparation process of the lead electroplating electrolyte used in the lead electroplating is: a calculated amount of basic lead carbonate is mixed with water to form a paste, added to a calculated amount of fluoroboric acid solution, and diluted with water to generate a lead fluoroborate solution.

[0018] Furthermore, at a current density of 10-40 mA / cm 2 , at a temperature of 28-32°C, lead is electrodeposited on the porous foam carbon substrate after chemical copper plating.

[0019] The foam carbon composite coating electrode is obtained by the preparation method.

[0020] A lead liquid flow battery comprises a negative electrode, wherein the negative electrode is the foam carbon composite coating electrode.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] The present invention greatly improves the conductivity of the negative electrode compared with the traditional carbon polymer graphite plate electrode by sequentially compounding a chemical copper plating intermediate layer and an electrochemically deposited lead layer on the foam carbon; the intermediate copper plating layer enhances the bonding strength with the outer layer of the electrochemically deposited lead in the form of metal bonds and solid solution strengthening, and the outer layer of the electrode electrochemically deposited lead has a higher bonding strength with the negative electrode storage Pb layer after the battery is charged, which can avoid the shedding of the storage deposit layer. The porous structure of the foam carbon composite coating electrode of the present invention has a larger specific surface area than the traditional carbon polymer graphite plate electrode, thereby greatly improving the storage capacity of the battery. The outer layer of the electrode electrochemically deposited lead of the present invention has a more negative hydrogen evolution potential and a smaller corrosion current density, thereby greatly reducing the side reactions in the electrode reaction process and the stability of the electrode operation. Compared with the traditional carbon polymer graphite plate electrode, the composite coating electrode of the present invention has no obvious edges and corners and tips, which greatly eliminates the tip effect of the electrodeposition process and inhibits the dendrite growth of the negative electrode storage deposit layer Pb.

[0023] Furthermore, the roughening method of the present invention is improved over the prior art, and the porous foam carbon substrate is roughened by concentrated acid etching, and the roughening is performed by ultrasonication for 10-30 minutes in nitric acid with a mass fraction of 55%-75% at room temperature. The immersion concentrated acid etching of the present invention can improve the uniformity of roughening, and this method can be used for complex porous structures, while physical grinding has the disadvantages of environmental pollution and the inability to roughen complex parts.

[0024] Furthermore, the sensitizer of the present invention adds concentrated HCl and trace tin particles on the basis of the prior art SnCl2. Dissolving SnCl2 in the HCl solution can inhibit the premature hydrolysis of SnCl2. Adding a small amount of tin particles can inhibit the oxidation failure of the sensitizer caused by the action of the oxidant and long-term exposure to air and light, thereby maintaining the Sn 2+ and Sn 4+ stability.

[0025] Furthermore, the activation solution of the present invention adds concentrated HCl on the basis of the prior art PdCl2. The concentrated HCl is dissolved in a small amount of water in advance, and then the PdCl2 is dissolved in a dilute HCl solution, which can inhibit the premature hydrolysis of PdCl2 and ensure the effectiveness of activation.

[0026] Furthermore, a pH buffer, adsorbent activated carbon and EDTA are added to the chemical copper plating solution of the present invention. When formaldehyde is used as a reducing agent, it needs to be carried out under alkaline conditions. The NaOH added in the present invention is to maintain the pH value of the plating solution and enable formaldehyde to fully exert its reducing effect. The adsorbent activated carbon can adsorb impurities and harmful substances in the plating solution, improve the electroplating effect and process quality, make the coating non-brittle and prevent the bottom layer from blooming. As the plating proceeds, the surface of the plated copper is prone to passivation when the pH value of the plating solution decreases or the temperature is too high, which sometimes stops the reaction, so adding a small amount of EDTA can prevent copper passivation.

[0027] Furthermore, in the present invention, the pretreated porous foam carbon substrate is pre-wetted with water and then subjected to chemical copper plating. The substrate is wetted in advance to ensure the hydrophilicity of each position, which is beneficial to ensure the uniformity of the plating thickness, bonding performance and uniformity of the stress distribution of the coating at each position.

[0028] Furthermore, the present invention refines the parameter conditions of lead electrodeposition and improves the operating details compared with the prior art. The anode lead with a purity higher than 99.9% is selected to avoid the generation of a large amount of insoluble anode slag, and an anode bag is wrapped around the anode to prevent the anode slag from falling into the solution and affecting the quality of the electrodeposited layer.

[0029] Further, the calculated amount of basic lead carbonate is mixed with water to form a paste, which is slowly added to the calculated amount of fluoroboric acid solution, and water is slowly added to dilute it to generate a lead fluoroborate solution. This operation is beneficial to reducing dust pollution in the environment, reducing the large amount of reaction heat generated during the preparation of the plating solution, and preventing the decomposition and failure of the plating solution.

[0030] Furthermore, precise control of current density and temperature can obtain high-quality electrodeposition layers, otherwise coarse particles or dendrite growth are likely to occur.

[0031] The foamed carbon composite coating electrode proposed in the present invention can realize the multifunctionalization of the negative electrode of the lead liquid flow battery, improve and enhance various physical and chemical properties, thereby greatly improving the charge and discharge cycle efficiency and storage capacity of the lead liquid flow battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 The pretreatment steps of foam carbon are: (a) degreasing; (b) roughening; (c) sensitization; (d) activation;

[0033] Figure 2 The actual object (a) and microscopic morphology (b) of carbon foam after chemical copper plating;

[0034] Figure 3 The actual object (a) and microscopic morphology (b) of the foam carbon composite coating electrode after electrodeposition of lead + chemical copper plating;

[0035] Figure 4 SEM images: (a) carbon foam morphology; (b) carbon foam composite coating electrode morphology; (b) carbon foam composite coating electrode cross-sectional morphology;

[0036] Figure 5 Current-time diagram for the specific surface area test of carbon foam composite coating electrode (CFCC-E) and carbon polymer graphite plate electrode (GE);

[0037] Figure 6 Cross-sectional morphology of the negative electrode Pb deposition layer on (a) carbon foam composite coating electrode and (b) carbon polymer graphite plate electrode;

[0038] Figure 7 Cycling efficiency of lead flow battery with foam carbon composite coating electrode and carbon polymer graphite plate electrode as negative electrode respectively;

[0039] Figure 8 The electrochemical impedance (a) and linear scanning curve (b) of the foam carbon composite coating electrode and the carbon polymer graphite plate electrode of Example 3;

[0040] Fig. 9 The microscopic morphology of the foam carbon chemical copper plating layer of Example 3 (a), Comparative Example 1 (b), Comparative Example 2 (c), and Comparative Example 3 (d);

[0041] Fig.10 The microscopic morphology of the chemically plated copper layer prepared in Example 3 (a) and Comparative Example 4 (b);

[0042] Fig.11The microscopic morphology of the chemically plated copper layer prepared in Example 3 (a) and Comparative Example 5 (b);

[0043] Fig.12 These are the charge and discharge voltage curves when the foam carbon composite coating electrode and the carbon polymer graphite plate electrode of Examples 1, 2, and 3 are respectively the negative electrodes of the lead liquid flow battery. DETAILED DESCRIPTION

[0044] In order to further understand the present invention, the present invention is described below in conjunction with embodiments. These descriptions are only to further explain the features and advantages of the present invention and are not intended to limit the claims of the present invention.

[0045] The method for preparing the foam carbon composite coating electrode of the present invention is to chemically plate copper and electrolytically deposit lead on a porous foam carbon substrate in sequence to prepare the foam carbon composite coating electrode. The preparation method comprises three steps: pretreatment of the porous foam carbon substrate; chemical copper plating and electrolytic lead deposition.

[0046] The method for preparing the foam carbon composite coating electrode of the present invention specifically comprises the following steps:

[0047] a. Pretreatment of porous carbon foam substrate: the porous carbon foam substrate is subjected to degreasing, roughening, sensitization and activation treatments in sequence; and then dried for later use, such as Figure 1 .

[0048] The degreasing process is as follows: the porous carbon foam substrate is immersed in an alkaline degreasing liquid at 60-70° C. for 20-30 minutes; the formula of the alkaline degreasing liquid is NaOH (34-42 g / L) + Na2CO3 (27-33 g / L) + Na3PO4 (21-38 g / L).

[0049] The roughening is to roughen the porous carbon foam substrate by concentrated acid etching, specifically: roughen the deoiled porous carbon foam substrate in nitric acid with a mass fraction of 55%-75% at room temperature, ultrasonic time: 10-30min, and then wash with water.

[0050] The sensitization is specifically as follows: the roughened porous foam carbon matrix is ​​treated in a sensitizing solution for 10-20 minutes, during which time the foam carbon matrix is ​​continuously stirred with a magnetic stirrer and is slightly shaken from time to time to allow the catalytic water film to be evenly adsorbed, followed by water washing; the sensitizing solution is formulated with concentrated HCl (40-55ml / L), SnCl2 (30-40g / L) and trace tin particles (4-8 particles). When preparing the sensitizing solution, first dissolve concentrated HCl in a small amount of water, and then dissolve SnCl2 in the HCl solution, which can inhibit the premature hydrolysis of SnCl2;

[0051] The activation treatment is specifically as follows: activating the sensitized porous foam carbon substrate in an activation solution at room temperature for 15-35 minutes, taking it out and hanging it naturally without washing it with water; the activation solution formula is PdCl2 (0.53-0.62g / L) and concentrated HCl (45-50ml / L).

[0052] b. Chemical copper plating on the pretreated porous foam carbon substrate: first, prepare an improved chemical copper plating solution containing a main salt, a complexing agent, a reducing agent, a pH adjuster, a stabilizer and other additives; transfer the chemical copper plating solution to a clean plating tank, start the stirring device, maintain 50-80r / min, hang the pretreated porous foam carbon substrate for plating, plating for 30-50min, take out, wash with water, dry and standby, such as Figure 2 .

[0053] The improved chemical copper plating solution comprises 20-25 g / L of copper sulfate (CuSO4·5H2O), 40-50 ml / L of formaldehyde solution (HCHO) with a mass concentration of 24%-37%, 70-100 g / L of potassium sodium tartrate (KNaC4H4O6), 10-15 g / L of sodium hydroxide (NaOH), 0.15-0.75 g / L of 2-mercaptobenzothiazole (MBT), 1-3 g / L of activated carbon and 0.1-0.5 g / L of EDTA.

[0054] When preparing the chemical copper plating solution, first dissolve all solid chemical raw materials (CuSO4, KNaC4H4O6, NaOH and EDTA) separately into concentrated aqueous solutions in advance; when the temperature is stable at room temperature, first mix the CuSO4 solution with the potassium sodium tartrate complexing agent solution, then slowly add the NaOH solution and EDTA solution under stirring, and finally add activated carbon to the solution; continue stirring and heating the solution to 50-65°C and keep it warm for 1.5-2.5h before filtering it carefully; add other additives MBT and formaldehyde solution to the treated solution; adjust the pH value of the chemical copper plating solution to the specified value of 12±1 with a dilute NaOH solution.

[0055] When chemically plating copper on the pretreated porous foam carbon substrate, the pretreated porous foam carbon substrate is moistened with deionized water 20-40 minutes in advance, and then immersed in a 25-30° C. chemical copper plating solution for 10-30 minutes for plating, and must not be taken out during the process.

[0056] c. Electrodeposition of lead on the porous carbon foam substrate after chemical copper plating: firstly, prepare an improved electroplating lead electrolyte, then construct a cathode / anodic electrodeposition device and materials, and finally, electroplating lead on the porous carbon foam substrate after chemical copper plating under specified conditions, such as Figure 3 .

[0057] The improved lead electroplating electrolyte comprises 200-280 g / L of fluoroboric acid (HBF4, mass concentration 40%-60%) solution, 110-160 g / L of basic lead carbonate (2PbCO3·Pb(OH)2), and 0.2-0.5 g / L of peptone.

[0058] The improved lead electroplating electrolyte preparation method comprises the following steps: mixing a calculated amount of basic lead carbonate with water to form a paste, slowly adding the paste into a calculated amount of fluoroboric acid solution, and slowly adding water to dilute the solution to generate a lead fluoroborate solution; then adding dissolved peptone to improve the crystallization quality of the coating, and filtering to obtain the lead electroplating electrolyte.

[0059] The cathode / anode electrodeposition device and materials are constructed by selecting anode lead with a purity higher than 99.9% to avoid generating a large amount of insoluble anode slag, and an anode bag is wrapped outside the anode lead to prevent the anode slag from falling into the solution.

[0060] Preferably at a current density of 10-40 mA / cm 2 Under the precise control of temperature of 28-32℃, lead is electrodeposited on the porous foam carbon substrate after chemical copper plating, otherwise dendrites will form at the edge of the electrode and the crystalline structure of the coating will be coarse (electrodeposition outside of this parameter condition is likely to lead to dendrite growth and coarse grains, and the quality of the obtained electrodeposited layer is not high); during the electrodeposition process, mechanical stirring at 110-150r / min is used to make the ions in the plating solution evenly distributed to prevent insoluble impurities from causing burrs in the coating.

[0061] The flow battery system selected for the charge and discharge test in the following examples is a lead flow battery. The lead flow battery is described in detail as follows:

[0062] 1. It is composed of single battery;

[0063] 2. The battery electrode area is 16cm 2 ;

[0064] 3. The vanadium ion concentration in the lead electrolyte solution is 1.5 mol / L and the methanesulfonate concentration is 0.9 mol / L;

[0065] 4. The current density of the battery constant current charge and discharge is 20mA / cm 2 ;

[0066] 5. The charge and discharge cut-off values ​​of the single cell are 1.85V and 1.0V respectively;

[0067] 6. The electrolyte volume is 160mL.

[0068] Example 1

[0069] (1) Pretreatment of porous carbon foam substrate: The porous carbon foam substrate with a size of 20×40×5 mm and a PPI (pores per inch) of 50 was immersed in an alkaline degreasing solution of NaOH (42 g / L) + Na2CO3 (33 g / L) + Na3PO4 (38 g / L) at 70°C for 30 min for degreasing; the degreasing porous carbon foam substrate was coarsened in 75% nitric acid at room temperature, ultrasonicated for 30 min, and then washed with water; the coarsened carbon foam substrate was The porous foam carbon substrate was treated in a sensitizing solution of concentrated HCl (55 ml / L) + SnCl2 (40 g / L) + 8 tin particles for 20 min, during which the foam carbon substrate was continuously stirred with a magnetic stirrer and slightly shaken from time to time to make the catalytic water film adsorbed evenly, and then washed with water; the sensitized porous foam carbon substrate was activated in an activation solution of PdCl2 (0.62 g / L) + concentrated HCl (50 ml / L) at room temperature for 35 min, taken out and naturally hung, and dried for use;

[0070] (2) Electroless copper plating on the pretreated porous foam carbon substrate: prepare an electroless copper plating solution with the formula of CuSO4·5H2O25g / L+37% HCHO 50ml / L+KNaC4H4O6 100g / L+NaOH 15g / L+MBT 0.75g / L+activated carbon 3g / L+EDTA 0.5g / L; wet the pretreated porous foam carbon substrate with deionized water 40min in advance, immerse it in the 30°C electroless copper plating solution, and plate it for 50min at a stirring rate of 80r / min, then take it out, wash it with water, and dry it for standby use;

[0071] (3) Electrodeposition of lead on the porous foam carbon substrate after chemical copper plating: preparing an improved lead plating electrolyte with a formula of 60% HBF4 280 g / L + 2PbCO3·Pb(OH)2 160 g / L + peptone 0.5 g / L; constructing a cathode / anodic electrodeposition device and materials, selecting an anode lead with a purity higher than 99.99% to avoid generating a large amount of insoluble anode slag, and wrapping an anode bag outside the anode to prevent the anode slag from falling into the solution; at a current density of 40 mA / cm 2 Under the precise control of temperature at 32°C, lead was electrodeposited on the porous foam carbon substrate after chemical copper plating. During the electrodeposition process, mechanical stirring at 150r / min was used to ensure uniform distribution of ions in the plating solution.

[0072] Example 2

[0073] (1) Pretreatment of porous carbon foam substrate: The porous carbon foam substrate with a PPI (pores per inch) of 20×40×5 mm and a size of 50 was immersed in an alkaline degreasing solution of NaOH (34 g / L) + Na2CO3 (27 g / L) + Na3PO4 (21 g / L) at 60°C for 20 min for degreasing; the degreasing porous carbon foam substrate was coarsened in nitric acid with a mass fraction of 55% at room temperature, ultrasonicated for 10 min, and then washed with water; the coarsened carbon foam substrate was The porous foam carbon substrate was treated in a sensitizing solution of concentrated HCl (40 ml / L) + SnCl2 (30 g / L) + 4 tin particles for 10 min, during which the foam carbon substrate was continuously stirred with a magnetic stirrer and slightly shaken from time to time to make the catalytic water film adsorbed evenly, and then washed with water; the sensitized porous foam carbon substrate was activated in an activation solution of PdCl2 (0.53 g / L) + concentrated HCl (45 ml / L) at room temperature for 15 min, taken out and naturally hung, and dried for use;

[0074] (2) Electroless copper plating on the pretreated porous foam carbon substrate: prepare an electroless copper plating solution with the formula of CuSO4·5H2O20g / L+37% HCHO 40ml / L+KNaC4H4O6 70g / L+NaOH 10g / L+MBT 0.15g / L+activated carbon 1g / L+EDTA 0.1g / L; wet the pretreated porous foam carbon substrate with deionized water 20min in advance, immerse it in the 25°C electroless copper plating solution, and plate it for 30min at a stirring rate of 50r / min, then take it out, wash it with water, and dry it for standby use;

[0075] (3) Electrodeposition of lead on the porous foam carbon substrate after chemical copper plating: preparing an improved lead plating electrolyte with a formula of 40% HBF4200g / L+2PbCO3·Pb(OH)2 110g / L+peptone 0.2g / L; constructing a cathode / anodic electrodeposition device and materials, selecting an anode lead with a purity higher than 99.99% to avoid generating a large amount of insoluble anode slag, and wrapping an anode bag outside the anode lead to prevent the anode slag from falling into the solution; at a current density of 10mA / cm 2 Under the precise control of temperature at 28°C, lead was electrodeposited on the porous foam carbon substrate after chemical copper plating. During the electrodeposition process, mechanical stirring at 110r / min was used to ensure uniform distribution of ions in the plating solution.

[0076] Example 3

[0077] (1) Pretreatment of porous carbon foam substrate: The porous carbon foam substrate with a size of 20×40×5 mm and a PPI (pores per inch) of 50 was immersed in an alkaline degreasing solution of NaOH (38 g / L) + Na2CO3 (30 g / L) + Na3PO4 (30 g / L) at 65°C for 25 min for degreasing; the degreasing porous carbon foam substrate was roughened in nitric acid with a mass fraction of 65% at room temperature, ultrasonically treated for 20 min, and then washed with water; the roughened carbon foam substrate was The porous carbon foam substrate was treated in a sensitizing solution of concentrated HCl (48 ml / L) + SnCl2 (35 g / L) + 6 tin particles for 20 min, during which the carbon foam substrate was continuously stirred with a magnetic stirrer and slightly shaken from time to time to make the catalytic water film adsorbed evenly, and then washed with water; the sensitized porous carbon foam substrate was activated in an activation solution of PdCl2 (0.58 g / L) + concentrated HCl (47 ml / L) at room temperature for 25 min, taken out and naturally hung, and dried for use;

[0078] (2) Electroless copper plating on the pretreated porous foam carbon substrate: prepare an electroless copper plating solution with the formula of CuSO4·5H2O22.5g / L+37% HCHO 45ml / L+KNaC4H4O6 85g / L+NaOH 12.5g / L+MBT 0.45g / L+activated carbon 2g / L+EDTA0.3g / L; wet the pretreated porous foam carbon substrate with deionized water 30min in advance, immerse it in the 27.5℃ electroless copper plating solution, and plate it for 40min at a stirring rate of 65r / min, then take it out, wash it with water, and dry it for standby use;

[0079] (3) Electrodeposition of lead on the porous foam carbon substrate after chemical copper plating: preparing an improved lead plating electrolyte with a formula of 50% HBF4 240 g / L + 2PbCO3·Pb(OH)2 135 g / L + peptone 0.35 g / L; constructing a cathode / anodic electrodeposition device and materials, selecting an anode lead with a purity higher than 99.99% to avoid generating a large amount of insoluble anode slag, and wrapping an anode bag outside the anode to prevent the anode slag from falling into the solution; at a current density of 25 mA / cm 2 Under the precise control of temperature at 30°C, lead was electrodeposited on the porous foam carbon substrate after chemical copper plating. During the electrodeposition process, mechanical stirring at 130r / min was used to ensure uniform distribution of ions in the plating solution.

[0080] Comparative Example 1

[0081] Based on the operation process of Example 3, the roughening method adopts traditional physical grinding for comparison, and other experimental conditions and processes are the same.

[0082] Comparative Example 2

[0083] Based on the operation process of Example 3, the sensitization process was compared without adding concentrated HCl and trace tin particles, and the activation process was compared without adding concentrated HCl. Other experimental conditions and processes were the same.

[0084] Comparative Example 3

[0085] Based on the operating process of Example 3, the chemical copper plating solution was compared without adding adsorbent activated carbon, and other experimental conditions and processes were the same.

[0086] Comparative Example 4

[0087] Based on the operation process of Example 3, the substrate before chemical copper plating was not pre-wetted for comparison, and other experimental conditions and processes were the same.

[0088] Comparative Example 5

[0089] Based on the operating procedures of Example 3, the lead electrodeposition process selected anode lead with a purity of 99%, and the anode lead was not wrapped with an anode bag for comparison. Other experimental conditions and procedures were the same.

[0090] The foamed carbon composite coating electrode obtained by the present invention is used to detect its physical and chemical properties; and is used as a negative electrode material of a lead liquid flow battery to detect the battery charging and discharging performance.

[0091] As shown in Table 1, the conductivity and specific surface area of ​​Examples 1, 2, 3 and the carbon polymer graphite plate electrode, the copper plating layer in the middle of the foam carbon composite coating electrode significantly improves the conductivity of the electrode, among which the electrode obtained with moderate preparation parameters in Example 3 has the largest specific surface area and conductivity.

[0092] Table 1

[0093]

[0094] As shown in Table 2, the charge and discharge capacity of the carbon polymer graphite plate electrode for 1, 5, 10 and 20 charge and discharge cycles of Examples 1, 2, 3 and carbon polymer graphite plate electrodes is found to be continuously reduced in charge and discharge capacity with the extension of the number of cycles, indicating that a deposited layer falls off from the electrode into the electrolyte and cannot be reduced to active ions dissolved in the electrolyte, resulting in a continuous decrease in the concentration of active ions in the electrolyte. However, as the number of cycles of Examples 1, 2 and 3 increases, the charge capacity and discharge capacity decay slowly, indicating that they have good interfacial bonding strength and deposition / dissolution reversible activity. This is because the key copper plating layer of the novel electrode in Example 3 enhances the bonding strength with the electrodeposited lead in the form of metal bonds and solid solution strengthening, and the electrodeposited lead coating can achieve good bonding with the same metal of lead after the negative electrode is charged, thereby reducing the discharge capacity loss caused by the fall of the negative electrode lead.

[0095] Table 2

[0096]

[0097]

[0098] Figure 4 The microscopic morphology of porous foam carbon, foam carbon composite coating electrode of Example 3 and cross section of foam carbon composite coating electrode of Example 3. The porous foam carbon provides a porous structure and a matrix skeleton, and the porous structure is not changed after copper plating and lead electrodeposition, and the copper layer and the lead layer are wrapped on the surface of the porous structure, eliminating the sharp points and making the surface smooth.

[0099] Figure 5 The cross-sectional morphology of the negative electrode Pb deposition layer after charging on the foam carbon composite coating electrode and the carbon polymer graphite plate electrode in Example 3. The lead deposition on the foam carbon composite coating electrode is smooth and tightly wrapped on the electrode skeleton. No obvious dendrite protrusions are observed in the cross section. This is because after copper plating and lead electrodeposition, the foam carbon surface becomes smooth and the curvature increases. The tip effect is significantly reduced during the battery charging and discharging process, making it difficult for Pb to grow dendrites. However, the lead deposition on the carbon polymer graphite plate electrode is loose and not dense, and the dendrite growth is obvious along the direction perpendicular to the electrode surface in the cross section, and the particle size gradually increases, which is related to its conductivity and edge angles.

[0100] Figure 6 The cycle efficiency of the lead liquid flow battery when the foam carbon composite coating electrode and the carbon polymer graphite plate electrode are respectively the negative electrode in Example 3, the coulomb, voltage and energy efficiency when the foam carbon composite coating electrode is the negative electrode are respectively stable at 97.5% ± 1.0, 92% ± 0.5, and 90% ± 1.0. The carbon polymer graphite plate electrode is respectively stable at 92.5% ± 2.0, 87.5% ± 1.0, and 82% ± 2.0. In addition, the fluctuation range of the three efficiencies of the lead liquid flow battery with the foam carbon composite coating electrode as the negative electrode is significantly smaller than that of the traditional carbon polymer graphite plate electrode, indicating the stability of the redox reaction process of the new foam carbon composite coating electrode, which is based on the excellent physicochemical properties of the new foam carbon composite coating electrode, including conductivity, interface bonding strength, reversible activity, corrosion resistance, specific surface area, etc.

[0101] Figure 7 The potentiodynamic polarization curves, corrosion current density and surface corrosion morphology of the foam carbon composite coating electrode and carbon polymer graphite plate electrode of Example 3 are shown in Figure 3. (a) The corrosion current density of the foam carbon composite coating electrode of Example 3 is 0.71×10 -6 A cm -2 , (b) 0.35×10 -5 Acm -2The corrosion current density of the foam carbon composite coating electrode is less than that of the carbon polymer graphite plate electrode, indicating that the foam carbon composite coating electrode is more corrosion-resistant and the lead on the surface forms a protective lead salt film in the acidic solution.

[0102] Figure 8 The electrochemical impedance and linear scanning curves of the foam carbon composite coating electrode and the carbon polymer graphite plate electrode in Example 3. (a) The results show that the negative lead on the foam carbon composite coating electrode after charging has a smaller particle size and higher redox activity, a smaller electrochemical polarization overpotential of the electrode, a smaller charge transfer impedance, and a faster electrode reaction rate. (b) It shows that the foam carbon composite coating electrode has a larger hydrogen evolution overpotential, which reduces the occurrence of hydrogen evolution side reactions.

[0103] The experimental results of Comparative Examples 1, 2, and 3 are as follows: Fig. 9 (a) is the foam carbon chemical copper plating layer prepared in Example 3, which is tightly bonded. Fig. 9 (b) is the chemical copper plating layer of the foam carbon after traditional physical polishing in comparative example 1. The layer is not tightly bonded to the foam carbon substrate and cracks appear on the cross section, which greatly affects the conductivity of the electrode. Fig. 9 (c) is the comparison example 2. Concentrated HCl and trace tin particles are not added in the sensitization process, and concentrated HCl is not added in the activation process. It is found that under the same plating conditions, the thickness of the chemical copper plating layer in Example 3 is about 3μm, while the chemical copper plating layer in Comparative Example 2 is only about 1μm. This shows that the addition of concentrated HCl and trace tin particles in the sensitization process and the addition of concentrated HCl in the activation process seriously affect the stability, efficiency and rapidity of the chemical copper plating process. Fig. 9 (a) is the chemical copper plating layer in Example 3, Fig. 9 (d) is the chemical copper plating layer in the chemical copper plating solution of comparative example 3 without adding activated carbon as an adsorbent. By comparison, it is found that the cross-sectional morphology of the copper plating layer obtained by the chemical copper plating solution of comparative example 3 has coarse and uneven particles, and the electrical conductivity is reduced, making it difficult to obtain a high-quality copper plating layer.

[0104] Comparative Example 4 Experimental results, such as Fig.10 (a) and (b) are respectively the chemical copper plating layer of Example 3 and the chemical copper plating layer obtained without pre-wetting the substrate before chemical copper plating in Comparative Example 4. By comparison, it is found that without pre-wetting, the hydrophilicity of each position of the substrate and the distribution of active sites after activation are different, which makes the thickness and stress distribution of the plating layer uneven, resulting in cracks in the copper plating layer.

[0105] Comparative Example 5 Experimental results, such as Fig.11(a) (b) are examples 3 and 5 respectively. In the lead electrodeposition process, an anode lead with a purity of 99% is selected, but an anode bag is not wrapped outside. The results show that the electrodeposited lead layer in example 3 is uniform and dense, and the particles are fine. However, the electrodeposited lead particles in comparative example 5 are coarse, and the adjacent foam carbon skeleton is connected and coated, thereby reducing the specific surface area of ​​the electrode. The main reason is that the purity of the anode lead is low, and the anode bag is not used for wrapping, resulting in the shedding of impurities and attachment to the cathode, forming nucleation growth sites, and accelerating the coarse growth of grains.

[0106] Fig.12 The charge and discharge voltage curves of Examples 1, 2, and 3 when the foamed carbon composite coating electrode and the carbon polymer graphite plate electrode are respectively the negative electrodes of the lead liquid flow battery. It can be seen from the figure that the foamed carbon composite coating electrodes of Examples 1, 2, and 3 have low charging voltages and high discharge voltages, indicating that they have high electrical conductivity and have the smallest polarization overpotential. The carbon polymer graphite plate electrode has a large resistance, thus a high polarization overpotential, and has a lower voltage efficiency. Among the foamed carbon composite coating electrodes of Examples 1, 2, and 3, Example 3 has the best charge and discharge voltage value, and therefore has the highest voltage efficiency.

Claims

1. A method for preparing a foam carbon composite coating electrode, characterized in that: The porous carbon foam substrate is sequentially electrolessly plated with copper and then electroplated with lead to prepare a carbon foam composite coating electrode.

2. The method for preparing a foamed carbon composite coating electrode according to claim 1, characterized in that: include: The porous foam carbon substrate is sequentially pretreated by degreasing, roughening, sensitizing and activating; Electroless copper plating on the pretreated porous carbon foam substrate; Electrodeposition of lead on porous carbon foam substrate after electroless copper plating.

3. The method for preparing a foamed carbon composite coating electrode according to claim 2, characterized in that: The coarsening is specifically as follows: the deoiled porous foam carbon matrix is ​​coarsened by ultrasonic treatment in nitric acid with a mass fraction of 55% to 75% at room temperature for 10 to 30 minutes.

4. The method for preparing a foamed carbon composite coating electrode according to claim 2, characterized in that: The sensitization is specifically as follows: treating the roughened porous foam carbon substrate in a sensitizing solution for 10-20 minutes, and then washing with water; the formula of the sensitizing solution is: concentrated HCl 40-55ml / L, SnCl2 30-40g / L and tin particles 4-8 particles / L.

5. The method for preparing a foamed carbon composite coating electrode according to claim 2, characterized in that: The activation treatment is specifically as follows: activating the sensitized porous foam carbon substrate in an activation solution at room temperature for 15-35 minutes, and then taking it out to dry naturally; the activation solution formula is: PdCl2 0.53-0.62g / L and concentrated HCl 45-50ml / L.

6. The method for preparing a foamed carbon composite coating electrode according to claim 2, characterized in that: The pretreated porous foam carbon substrate is pre-wetted with water and then subjected to chemical copper plating.

7. The method for preparing a foamed carbon composite coating electrode according to claim 2, characterized in that: The chemical copper plating solution used in the chemical copper plating is formulated as follows: 20-25 g / L copper sulfate, 40-50 ml / L 24%-37% formaldehyde solution, 70-100 g / L potassium sodium tartrate, 10-15 g / L sodium hydroxide, 0.15-0.75 g / L 2-mercaptobenzothiazole, 1-3 g / L activated carbon, and 0.1-0.5 g / L EDTA.

8. The method for preparing a foamed carbon composite coating electrode according to claim 2, characterized in that: The electrodeposited lead uses anode lead with a purity higher than 99.9%, and an anode bag is wrapped outside the anode lead.

9. The method for preparing a foamed carbon composite coating electrode according to claim 2, characterized in that: The preparation process of the lead electroplating electrolyte used in the lead electroplating is: a calculated amount of basic lead carbonate is mixed with water to form a paste, added into a calculated amount of fluoroboric acid solution, and water is added to dilute to generate a lead fluoroborate solution.

10. The method for preparing a foamed carbon composite coating electrode according to claim 2, characterized in that: At a current density of 10-40 mA / cm 2 , at a temperature of 28-32°C, lead is electrodeposited on the porous foam carbon substrate after chemical copper plating.

11. A foamed carbon composite coating electrode obtained by the preparation method according to any one of claims 1 to 10.

12. A lead liquid flow battery, characterized in that: The lead flow battery comprises a negative electrode, wherein the negative electrode is the foam carbon composite coating electrode according to claim 11.